2011
DOI: 10.4028/www.scientific.net/amr.368-373.410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Compressive Bearing Capacity of High Strength Concrete-Filled Steel Tube Composite Columns

Abstract: To study axial compressive strength of high strength concrete-filled steel tube composite columns, tests of 18 specimens were carried out. Parameters of the specimens were the confinement index of concrete-filled steel tube, the cubic strength and the stirrup characteristic value of concrete outer of steel tube. Test results show that the concrete-filled steel tube and the reinforced concrete deformed simultaneously in the axial direction before and at the peak value of axial compressive force; after failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kang et al [22] and Cai et al [23] considered the strength of concrete, stirrup ratio, longitudinal reinforcement ratio, cross-section shape and steel ratio, and carried out axial compression tests of concrete-encased CFST composite columns. It is found that the steel ratio, the strength of concrete and the stirrup ratio are the main factors affecting the axial compression performance of concreteencased CFST composite column, and the bearing capacity of composite column increases with the increase of steel ratio.…”
Section: Axial Compression Performancementioning
confidence: 99%
“…Kang et al [22] and Cai et al [23] considered the strength of concrete, stirrup ratio, longitudinal reinforcement ratio, cross-section shape and steel ratio, and carried out axial compression tests of concrete-encased CFST composite columns. It is found that the steel ratio, the strength of concrete and the stirrup ratio are the main factors affecting the axial compression performance of concreteencased CFST composite column, and the bearing capacity of composite column increases with the increase of steel ratio.…”
Section: Axial Compression Performancementioning
confidence: 99%
“…This includes investigations into axial compression performance, seismic behavior, and bending performance. Kang et al [19] and Nie et al [20] studied the axial compression performance of the CFCST columns experimentally. Qian et al [21] and Ji et al [22] studied the seismic performance of the CFCST columns.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Kang, in order to study the axial compressive strength of CFST, made a series of tests for composite columns. And what the results showing is that the axial compressive ability is mainly associated with the factors including the limit index, the cubic strength and the stirrup characteristic value, etc [8]. In the same year, Cai published the latest development of high strength concrete filled steel tube structure technology in our country in Russian journals [9].…”
Section: Introductionmentioning
confidence: 99%